Leaky Wave Array in Full Planar Substrate with EBG-Based Wave Guiding Channel - Linghui Kong; Sen Yan; Vladimir Volskiy; Binke Huang; Guy A. E Vandenbosch (International Journal of Antennas and Propagation)
A new type of wave guiding structure is proposed is this paper. The guiding channel is developed on the full planar dielectric substrate and aligned with electromagnetic bandgap (EBG) units. Since the bandgap of these mushroom-like units is calculated with a coverage of the channel working band, these units are of great importance on ensuring the transmission efficiency and eliminating the coupling effect between channels. Then, this wave guiding structure is extended to the design of a six-element leaky wave antenna array with a complete size of 25.6 mm × 80.6 mm, which is working at Ku band from 12.0 GHz to 12.8 GHz and achieving a bandwidth of about 0.8 GHz, a gain of 11.36 dBi, and an efficiency of ca. 86.7% at 12.0 GHz. Within the working frequency band, this antenna topology achieves a frequency-dependent beam scanning in the forward directions, and it offers a potential for radar application on road speed detecting with low costs.